(untitled) (Alimentos Ciencia e Ingeniería, 2022)
Given the increase in production, the excessive use of plastic, and the negative impact it has on the environment, sustainable alternatives are being sought to replace this material; that is why there is a great demand for the development of new materials that are friendly to our mother earth. The current work aims to prepare bioplastic sheets made from banana peel as the primary raw material. A mixture of glycerin, corn starch, and vinegar (acetic acid) was added, resulting in brown biodegradable containers and sheets, similar to the results of other research using this biological material, and with more time to show signs of deterioration compared to other bioplastics.